Hubungan kedinamikan dalaman dengan keberkesanan pasukan maya: Satu tinjauan di organisasi bertaraf Koridor Raya Multimedia (MSC) yang terpilih - Aripin, Norizah; Mustafa, Hasrina; Hussein, Adnan (Universiti Kebangsaan Malaysia, 2014)
This study examines the internal relationship dynamics of virtual teams in terms of their usage frequency of communication media in virtual team effectiveness.Quantitative methods are employed through the distribution of 363 sets of questionnaires to experienced staff working in virtual teams based in Kuala Lumpur, Selangor, Penang and Kedah.The Spearman correlationtest was used to test the relationships between the frequent usage of communication media (phone calls, voice mail, fax, e-mail, instant messaging, audio conferencing, video conferencing, shared database system, and face to face communication) with virtual team effectiveness (team performance, team member satisfaction and quality of decision making made by the team).The study found that frequent phone calls, e-mails and having a shared database system have a significantly positive relationship upon virtual team effectiveness.The results also demonstrate that frequent face-to face communication and voice mail have a significantly negative impact on virtual team effectiveness.However, the use of fax, instant messaging, audio conferencing and video conferencing are not significantly correlated with virtual team effectiveness.Based on these findings, the use of phone calls, e-mail and shared database system contribute towards virtual team effectiveness.